Acupoint-tuina therapy promotes lactation in postpartum women with insufficient milk production who underwent caesarean sections. Issue 35 (August 2019) - Lu, Ping; Ye, Zhi-qi; Qiu, Jin; Wang, Xiao-yu; Zheng, Juan-juan
Abstract : Abstract: Breast milk is recognized and strongly recommended by the World Health Organization (WHO) as the optimal feeding for all babies. Breastfeeding is associated with better nutritional and non-nutritional outcomes when compared to formula feeding, and has proven health benefits to both infants and their mothers. This clinical research is to examine the feasibility and efficacy of Acupoint-Tuina therapy in treating postpartum women who underwent C-sections and suffered from insufficient milk production. The patients in the control group received standard medical care, while the patients in the Tuina group received Tuina therapy during the next 48 hours in addition to standard care, given once daily for 2 days. To evaluate the efficacy of Tuina therapy, patients of both groups were assessed for surface temperature of breasts, volume of breasts, volume of breast milk production, serum PRL level, and uterus recovery at various time points. Tuina therapy significantly increased the milk production when compared to the control group, for as much as 13-fold and 10-fold of that in the control group on the third and fourth postpartum days. In addition, Tuina therapy also significantly increased the full breast enlargement and the serum PRL level change, and decreased the breast surface temperature rise. Last but not the least, Tuina therapy also accelerated the post-surgery recovery of uterus. During the early postpartum days, Tuina therapy increases the milk production and promotes other physiological changes supporting lactation for postpartum women with C-section delivery and insufficient breast milk production. The novel intervention is warranted for further investigation and validation.